Employee perceptions of Occupational Health and Safety Standards (OHS) in the oil and gas industry in Malaysia / Abidah Saad… [et al.] - Saad, Abidah; Sandhu, Sukjeet Kaur; Gill, Ajitpall Singh; Tara Singh, Harpajan Singh; Syed Abu Bakar, Syarifah Mastura; Tirumalaisamy, Vikneswary (2023)
The purpose of the study is to explore the relationship between information and training, workplace environment and work safety inspection with the employee perceptions of occupational health and safety standards in the oil and gas industry in Malaysia. The population in this study are employees in oil and gas companies in Malaysia. The method used in this research was quantitative descriptive. Data was collected using questionnaires and Partial Least Squares Structural Equation Modelling (PLS-SEM) was used as the research tool in this study because it offers a higher degree of predictive power when sample sizes are limited or model structures are complex. Results suggest that information and training have the strongest relationship with employee perception followed by workplace environment and workplace safety inspection. For the hypothesis testing, two variables which are training and information and workplace environment have a significant relationship while work safety inspection doesn’t have a significant relationship with employee perception. This study has only focused on the employees that are under the oil and gas industry, and therefore could not be generalized to the other contexts. The time constrain also lead to low response rate. The online data collection method may have excluded workers in remote locations. The survey was entirely in English, making it challenging for non-English speakers. This study offers a number of important theoretical, practical and/or managerial implications. It has developed and tested the integrated model that examines how information and training, workplace environment and work safety inspection can influence the employee perceptions of occupational health and safety standards in the oil and gas industry in Malaysia. The research model is valid in explaining the factors that have contributed to employee perceptions of occupational health and safety standards in the oil and gas industry in Malaysia. In this light, understanding these factors will provide valuable insights on ways to enhance the operational and health standards in the Oil and Gas Industry. These would also benefit the related parties such as managers, staff, consumers, government agencies, organized labour teams and researchers.